B149 Determinants of length of stay following elective hip replacement surgery. (11th August 2022) - Matiaki, E; Lamont, E; Dunsmuir, C; Crawford, J; Desai, N; Zimmer, R; Luck, J
Abstract : Background and Aims: Our aim was to identify independent pre-operative factors that determine length of stay (LOS) following elective primary total hip replacement surgery in a large volume tertiary orthopaedic centre. Methods: Data for all patients undergoing elective primary total hip replacement in the Golden Jubilee National Hospital of Glasgow between 1st of January and 31st of December 2018 were prospectively collected; the database was supplemented with variables of interest. The cohort was divided in two groups by the median LOS, and the two group characteristics were compared statistically. A multivariate logistic regression was subsequently performed by including the statistically significant parameters arising from the univariate comparison. Analysis was performed with the use of SPSS. Results: Data for a total of 1746 patients were analysed. Of those 1014 (58.1%) were females. The median age was 68.3 years. Significant cardiopulmonary disease was identified in 318 (18.2%). The mean BMI was 29.6 (SD: 5.5) and the mean pre-operative haemoglobin was 136.5 g/L (SD: 13.7 g/L). The median LOS was 2 days with a cumulative inpatient stay of 4449 days. Age (OR: 1.036; 95% CI: 1.023–1.048), pre-operative haemoglobin (OR: 0.982; 95% CI: 0.973–0.991), gender (OR: 0.698; 95% CI: 0.545–0.894), ASA (OR: 1.828; 95% CI: 1.828–2.902) were found to be independent determinants of the LOS. Conclusions: Age, gender, pre-operative haemoglobin, and ASA are shown to be independent determinants of the LOS for patients undergoing elective primary total hip replacement surgery. On this basis, appropriate peri-operative planning can be undertaken to streamline patient selection and management for fast-tract hip replacement surgery.